Individualized antibiotic therapy in patients with ventilator‐associated pneumonia. Issue 1 (January 2017) - Yilmaz, Gürdal; Salyan, Sedat; Aksoy, Firdevs; Köksal, İftihar
Abstract : N/A: The optimal duration of the treatment of ventilator‐associated pneumonia (VAP) is still the subject of debate. While 1 week treatment has been reported as possibly sufficient, patients generally receive antibiotic therapy for 10 to 14 days. The purpose of our study was to investigate whether length of treatment in patients with VAP can be reduced with an individualized therapeutic strategy. The study was performed prospectively with patients diagnosed with VAP in our hospital's intensive care units between 1 January and 31 December 2015. Duration of antibiotic therapy was determined with 5 day clinical evaluation according to previously established criteria. Patients were divided into two groups depending on length of treatment, short (7‐10 days) and long treatment (>10 days). Nineteen patients received 7 to 10 day antibiotic therapy, and 30 received >10 day antibiotic therapy. Demographic and clinical characteristics, Glasgow Coma Scale score, CPIS and the PaO2 /FiO2 ratio at the time of diagnosis of VAP were statistically similar between the two groups ( P >0.05). A second VAP attack occurred post‐treatment in three patients receiving short‐term treatment and in four receiving long‐term treatment ( P =0.561). The numbers of antibiotic‐free days were 15.6±6.2 in the short‐term treatment group and 8.3±7.5 in the long‐term group ( P <0.0001). One of the patients receiving short‐term treatment died within 28 days after treatment, and four of the patients receiving long‐term treatment ( P =0.348) did so. The most commonly observed micro‐organisms in both groups were Acinetobacter baumannii and Pseudomonas aeruginosa . Short‐term treatment can be administered in cases with early clinical and laboratory response started on VAP treatment by considering individual characteristics and monitoring fever, CPIS, the PaO2 /FiO2 ratio, C‐reactive protein and procalcitonin values.